Strategi Guru Dalam Meningkatkan Keaktifan Belajar dan Minat Membaca Siswa Pada Mata Pelajaran Fiqih di MA Tahfidz Nurul Iman Karanganyar - Azka Zen, Millati; Mulyanto; Faridatul Ulfah, Yetty (Program Studi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah dam Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2023)
This study aims to determine what strategies the teacher applies in increasing studentlearning activeness and interest in reading in fiqh subjects, how the implementation ofstrategies implemented by teachers in increasing student learning activeness and interest inreading in fiqh subjects and what are the supporting and inhibiting factors in studentlearning activeness and interest in reading at MA Tahfidz Nurul Iman Karanganyar.In this study using descriptive qualitative research methods. The location of thisresearch is at MA Tahfidz Nurul Iman Karanganyar. The research subjects or informants of this research are teachers who teach Fiqh material at MA TAhfidz Nurul Iman Karanganyar,mudir MA Tahfidz Nurul Iman Karanganyar, wakasek student affairs and students at MATAhfidz Nurul Iman Karanganyar. The data collection techniques used in this research areinterviews, observation or observation, and documentation.The results of this study are, first, the strategies that teachers apply in increasingstudent learning activeness and interest in reading in fiqh subjects are teachers usingdiscussion methods, group study, question and answer and practical methods and lecturemethods. Second, the selection of strategies by teachers in increasing student learningactiveness and interest in reading in fiqh subjects has been implemented well, such as forexample active students when learning is taking place, among others: they actively askquestions with the teacher, do not pasid in discussions and are able to practice on thematerial that has been taught. Third, supporting factors in learning activeness and students'interest in reading at MA Tahfidz Nurul Iman Karanganyar, among others, namely: clean,conducive environment and away from crowded streets etc. Then, the inhibiting factors in theactiveness of learning and reading of students include: some students are often sleepy when inclass, easily feel bored when learning takes place, etc